Music Information Retrieval for Turkish Music: Problems, Solutions and Tools - Bozkurt, Baris; Gedik, Ali Cenk; Karaosmanoglu, M. Kemal (IEEE, 2009)
This study discusses differences between Turkish music and Western music from on information retrieval perspective. It proposes use of frequency histograms for various music information retrieval applications: automatic Ionic detection, makam classification, tuning analysis, theory-practice mismatch measurement. It announces a Matlab toolbox: Makam Toolbox 1.0 and a parametric database for Turkish music information retrieval research.
Keywords: Computer Science; Engineering; Telecommunications